Kualitas Beras dan Kandungan Gizi Tiga Genotipe Padi yang Dibudidayakan secara Organik dan Non Organik - Ajeng Aulia Martina; Dulbari Dulbari; Jaenudin Kartahadimaja; Subarjo Subarjo (Politeknik Negeri Lampung, 2024)
Rice is the main staple food for most Indonesians. Rice consumption in Indonesia is increasing along with population growth. Efforts to increase rice production continue to be carried out. Increasing production using external inputs in the form of chemical fertilizers and pesticides has resulted in a decrease in food quality and land degradation. Meeting food needs must be harmonized with environmental sustainability. Organic rice cultivation can improve the quality of agricultural products and be friendlier to the environment. This research aims to determine the quality of rice and the nutritional content of three rice genotypes cultivated organically and non-organically. The research was conducted at the Politeknik Negeri Lampung, in August 2022- April 2023. The research results showed that the quality of rice from three rice genotypes (red, white, black) in the organic cultivation system met the Premium Quality requirements, while in the non-organic cultivation system it met the Medium Quality requirements I SNI 6128:2020. The nutritional quality of the three rice genotypes was not significantly different in organic and non-organic cultivation systems Keywords: organic rice, brown rice, black rice, white rice, SNI 6128-2020